The use of construction and demolition waste as natural aggregate replacement - Cheong, Justin Wai Keong (2014)
Construction debris generated from structures or roadways that were demolished is traditionally disposed in the landfills. In Singapore where land is scarce and the environmental impact of disposing construction waste is large, concrete recycling prolongs the use of resources and cuts costs from construction materials.